Perfil, condições higiênicas e conhecimento de boas práticas de colaboradores de UANs do tipo self service e delivery no município de Itaqui - RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Good Handling Practices are procedures that must be adopted by food services to ensure hygienic-sanitary quality and conformity of prepared and / or handled food as required by health legislation. The present study aimed to know the profile, the hygienic conditions and to compare the knowledge of good practices of Uans employees of the self serviceedelivery type in the city of Itaqui - RS. The research consisted in the application of a checklist of Good Meal Handling Practices, based on ANVISA Directive No. 78/09, of January 30, 2009, on 13 closed questions on hygiene control of handlers, with the following definitions: Not, Yes, and Not applicable. A questionnaire with 25 questions about socioeconomic and socio demographic characteristics, knowledge about good practices of manipulation, training of the food handler and concepts of food safety was also used. For categorical variables, the chi square test was performed. For quantitative variables, mean, percentage, and t-test were performed. The data were evaluated in the program Statistical Package for Social Sciences (SPSS) version 22.0. They were considered statistically significant when p≤0.05, with a confidence interval of 95%. In this study it was observed that the majority of employees are female, aged 21 to 49 years, income of up to two minimum wages, with Incomplete high school, married, being the first job in the area of food and without knowledge of BP. The hygienic condition of the handlers did not present a difference between the self service and delivery type establishments, according to ordinance 78. Although most of the collaborators in the present study do not have knowledge about good handling practices, most perform adequate hygiene practices, as required by the BP, given the number of correct answers to the related questions, regardless of the type of service. Establishments evaluated the collaborators in their majority are young women, married, with low income, low education, and with low knowledge about BP. No statistically significant difference was observed in comparison to data comparisons between the service and delivery service groups.
Keywords: Higiene; Manipulação; Serviço de alimentação; Colaborador; Hygiene; Manipulation; Food service; Collaborator; CNPQ::CIENCIAS DA SAUDE